Vanishing twin syndrome is associated with first-trimester intrauterine hematoma in twin pregnancies after in vitro fertilization - Ge, Yimeng; Lai, Shaoyang; Li, Xiaoxue; Shi, Jing; Ma, Caihong; Zhao, Jie (Frontiers in Endocrinology, 2023)
Research question Is there an association between intrauterine hematoma (IUH), vanishing twin syndrome (VTS), and subsequent complications in twin pregnancies after in vitro fertilization (IVF)? What are the risk factors for these complications? Design Women who presented with two live gestational sacs following double embryo transfer were included. Patients with systematic diseases, artificial fetal reduction, and incomplete data were excluded. Further stratification of IUH pregnancies was performed according to IUH-related characteristics (i.e., volume, changing pattern, and relationship with fetal cardiac activities). The primary outcome was the incidence of VTS, while adverse outcomes in the surviving singleton and the gestational age of VTS were secondary outcomes. Results The incidence of IUH was 13.8%. A total of 1,078 twin pregnancies including 539 IUH pregnancies and 539 non-IUH pregnancies were included. IUH pregnancy was associated with higher risks of VTS (26.9% vs. 18.7%, p = 0.001) as well as a higher incidence of preterm birth (p = 0.001, crude OR = 1.98, 95% CI 1.28–3.09, adjusted OR = 1.19, 95% CI 1.09–1.24), threatened abortion (p < 0.001, crude OR = 9.12, 95% CI 2.90–28.69, adjusted OR = 6.63, 95% CI 1.69–14.67), and postpartum hemorrhage (p = 0.024, crude OR = 3.13, 95% CI 1.09–8.99, adjusted OR = 1.16, 95% CI 1.08–1.32) in the surviving singleton. There was no significant difference in risks of other complications. The absence of fetal cardiac activities at the diagnosis of IUH predicted VTS (p < 0.001, crude OR 4.67, 95% CI 3.67–5.78, adjusted OR 3.33, 95% CI 1.56–5.14) and fetal loss at smaller gestational age (7.81 ± 2.10 vs. 11.39 ± 5.60 weeks, p < 0.001), while an IUH with an increasing volume did not increase the risk of VTS but might induce threatened abortion in the surviving fetus (p < 0.001, crude OR 1.84, 95% CI 1.32–2.55, adjusted OR 1.72, 95% CI 1.13–2.13). Conclusions IUH was a risk factor for VTS in twin pregnancies following double embryo transfer and elevated the risks of threatened abortion, preterm birth, and postpartum hemorrhage in the surviving singleton. The absence of fetal cardiac activities at the diagnosis of IUH elevated the risks of VTS, while an IUH with an increasing volume was associated with threatened abortion without elevating the risks of VTS. An IUH diagnosed before the presence of fetal cardiac activities also resulted in an earlier miscarriage. The study suggests that attention be paid to twin pregnancies with first-trimester IUH to prevent VTS and subsequent adverse perinatal outcomes. Highlights First-trimester intrauterine hematoma (IUH) following double embryo transfer is associated with a higher incidence of vanishing twin syndrome (VTS) and elevated subsequent risk of threatened abortion, preterm birth, and postpartum hemorrhage in the surviving singleton. Other perinatal outcomes were not associated with the diagnosis of first-trimester IUH. The absence of fetal cardiac activities at the diagnosis of IUH was of predictive value toward VTS, while an IUH with an increasing size was associated with threatened abortion without elevating the risk of VTS. Incomplete fetal cardiac activities and earlier detection of an IUH might also predict miscarriage at smaller gestational age.